2017
DOI: 10.1002/btpr.2486
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to obtain cellulose nanocrystals and ethanol from eucalyptus cellulose pulp via the biochemical pathway

Abstract: The feasibility of integration of cellulosic ethanol production with the manufacture of cellulose nanofibers (CNF) and cellulose nanocrystals (CNC) was evaluated using eucalyptus cellulose pulp as feedstock and employing the biochemical route alone. For the enzymatic hydrolysis step, experimental central composite design (CCD) methodology was used as a tool to evaluate the effects of solids loading (SL) and enzymatic loading (EL) on glucose release and cellulose conversion. Glucose concentrations from 45 to 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 72 publications
(152 reference statements)
1
34
0
Order By: Relevance
“…In the particular case of CNFs production, the enzymatic hydrolysis is commonly followed by a mechanical step of fibrillation, such as homogenization [ 38 , 44 ], microfluidization [ 49 , 50 ], extrusion [ 25 , 51 ], and sonication [ 27 , 52 ], among others. Few studies have also reported no mechanical treatment step after hydrolysis [ 12 , 53 , 54 , 55 ], hence totally relying on the enzymes to produce the nanofibers.…”
Section: Nanocellulose Production By Enzymatic Hydrolysismentioning
confidence: 99%
See 3 more Smart Citations
“…In the particular case of CNFs production, the enzymatic hydrolysis is commonly followed by a mechanical step of fibrillation, such as homogenization [ 38 , 44 ], microfluidization [ 49 , 50 ], extrusion [ 25 , 51 ], and sonication [ 27 , 52 ], among others. Few studies have also reported no mechanical treatment step after hydrolysis [ 12 , 53 , 54 , 55 ], hence totally relying on the enzymes to produce the nanofibers.…”
Section: Nanocellulose Production By Enzymatic Hydrolysismentioning
confidence: 99%
“…A final aspect to also consider is that enzymatic extraction does not modify the surface chemistry of cellulose since no additional charges are introduced [ 103 ], usually resulting in a material with higher thermal stability [ 47 , 54 , 121 ]. As compared to sulfuric acid hydrolysis, this represents a clear advantage since the presence of sulfur groups leads to a negative surface charge [ 122 ].…”
Section: Nanocellulose Production By Enzymatic Hydrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…43 To avoid these problems, many researchers have studied alternative processes to obtain CNCs. Among them, we can highlight enzymatic hydrolysis, 44,45 enzymatic hydrolysis followed by acid hydrolysis, 46 ultrasonically assisted hydrolysis without 47 and with weak organic acids, 48 hydrolysis with oxidizing agents, 49 hydrolysis in subcritical water 50 and hydrolysis mediated by ionic liquids. 51…”
mentioning
confidence: 99%